Dendritic cells in the human vaginal mucosa can direct CD4+ T cell responses by expressing surface OX40L - Joo, HyeMee; Baert, Laurie; Yang, Agnes; Duluc, Dorothee; Yi, Johnny; Oh, SangKon (Frontiers in Immunology, 2025)
IntroductionImmunity in the vaginal mucosa (VM) is of critical importance for the protection from infections and cancers. Dendritic cells (DCs) are the major antigen-presenting cells that can induce and control T cell responses. Interestingly, VM Langerhans cells (vLCs) and VM CD1c+CD14- DCs (vDCs) polarize CD4+ T cells toward Th2-type. However, the mechanisms underlying Th2 polarization by vDCs remain unknown.MethodsOX40L expression was determined in the human VM tissue sections, followed by the measurement of OX40L expression on vLCs, CD1c+CD14- vDCs, and VM macrophages (vMØs) by flow cytometry. The roles of OX40L on vDC subsets in the induction of different types of CD4+ T cell responses were assessed.ResultsBoth vLCs and CD1c+CD14- vDCs express surface OX40L. Neutralizing OX40L with anti-OX40L antibody significantly decreased the frequency of Th2-type CD4+ T cells with a reduction of CD4+ T cell proliferation, while increasing the frequency of IL - 10-producing CD4+ T cell responses. Anti-OX40L did not affect vLC- or CD1c+CD14- vDC-induced Th1-type T cell responses. OX40L also contributed to the induction of IL - 21+CD4+ T cell responses by vLCs and CD1c+CD14- vDCs. In contrast to vLCs and CD1c+CD14- vDCs, vMØs expressed a minimal level of surface OX40L. Likewise, anti-OX40L did not significantly affect vMØ-induced CD4+ T cell responses.ConclusionsOX40L contributes to vLC- and CD1c+CD14- vDC-induced Th2 polarization. It also significantly affects the frequency of vLC- and CD1c+CD14- vDC-induced IL - 10+ and IL - 21+CD4+ T cells. This study provides new insights into the immunological landscape of the human VM tissues, with implications for the development of targeted immunomodulatory strategies at this mucosal site.